Is Immigration Good or Bad for the Economy? Analysis of Attitudinal Responses - Christian Dustmann; Ian Preston (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2004)
In this paper we study attitudinal responses of host country residents towards further immigration that are triggered by economic considerations. We develop an economic model motivating the empirical work that takes a broader view on these issues than previous papers. We provide empirical analysis that is based on data more specific and better suited to pick up the many channels of economic interest through which benefits and costs of immigration may be felt. Results support previous literature in establishing strong associations between individual characteristics and a wide range of responses to questions relating to perceived impact of immigrants on economic outcomes. Our analysis points to the importance of a wider view on channels of economic interest and the way these affect assessment of immigration.
Keywords: J2; J3; F2; 330; Migration; Effects of Immigration; Attitudes